Co-digestion of cow manure, food waste and intermittent input of fat - Neves, L. (2009)
Pulses of oil were added to completely mixed reactors fed with dairy cow manure and food waste, after achieving a stable performance at an organic loading rate of 4.6 ± 0.1 gCOD/(lreactor day), an oily waste effluent from a canned fish processing industry was fed in the form of pulses. The oil concentration rose up to 9, 12, 15 and 18 gCODoil/lreactor, after the pulse feeding in the reactor. The highest fat concentration of 18 gCODoil/lreactor promoted a persistent inhibition in the process of the continuous reactor, although in batch assays, the reactor content evidenced a capacity to degrade more oil and to degrade the accumulated organic matter. All the other pulses had a positive effect in the methane production. From a practical point of view, this work demonstrates that controlled intermittent inputs of oil can enhance the methane production in a co-digestion of cow manure and food waste.